En Torno a las Influencias Externas Sobre el Sistema Ionosfera-Atmósfera - Herraiz, Miguel; Kazimirovski, E. (Física de la Tierra, 2006)
Earth´s Magnetic Field is generated by many complex physical phenomena located in different parts of the planet and near-Earth space. Its temporal and spatial behaviour continuously reflects this extremely complicated origin, which is not yet totally known. The different sources of the geomagnetic field are closely linked together and with other geophysical processes, and none of these sources can be understood without considering these interactions. This is particularly the case when the ionosphere-atmosphere system is considered. This article reviews the interaction between this system, with a special emphasis on the Mesosphere-Lower Termosphere region, and the geomagnetic field. Forcing from below is also considered, and particular attention is paid to the controversial seismo-ionospheric coupling